Linear Analysis of Composite Steel Ribbed Deck by Grillage Method - Husain M. Husain; Sa'ad Kh. M. Al-Hadithy (Journal of Engineering and Sustainable Development, 2005)
This work is aimed to study the behaviour of composite top steel cover plate on steel beams running in two directions. Linear shear connection behaviour with partial interaction is assumed. The study assesses the effect of slip that will take place between cover steel plate and the steel beams when the composite deck is subjected to normal loads.The simplified grillage (or grid-framework) method is used to study the deflections and the moments in the grillage caused by the applied loads. The solution is approximate but gives acceptable accuracy when compared with more accurate methods such as the method of finite elements by using plane shell elements.Keywords: Composite deck, Grillage method, Shear connectors, Steel structure.